Documenting Racism African Americans in US Department of Agriculture Documentaries, 1921-42 - Winn, J. Emmett (Bloomsbury Academic, 2012)
From the silent era through the 1950s, the U.S. Department of Agriculture was the preeminent government filmmaking organization. In the United States, USDA films were shown in movie theaters, public and private schools at all educational levels, churches, libraries and even in open fields. For many Americans in the early 1900s, the USDA films were the first motion pictures they watched. And yet USDA documentaries have received little serious scholarly attention. The lack of serious study is especially concerning since the films chronicle over half a century of American farm life and agricultural work and, in so doing, also chronicle the social, cultural, and political changes in the United States at a crucial time in its development into a global superpower. Focusing specifically on four key films, Winn explicates the representation of African Americans in these films within the socio-political context of their times.